Squamous Cell Carcinoma of the Breast, a Rare Entity: Report of Case from Ouagadougou/Burkina Faso and Review of the Literature - Zongo, Nayi; Yaméogo, P. Bonaventure; Ouédraogo, Aimé Sosthène; Djigemdé, R. Adeline; Dem, Ahmadou (Asian Pacific Journal of Cancer Care, 2022)
Introduction: Squamous cell carcinoma (SCC) of the breast is a rare tumour. Histology and immunohistochemistry are the key to diagnosis. Treatment is similar to other breast cancers. Its prognosis is poor. We report our first documented case with the aim of describing our diagnostic and therapeutic features. Case report: A 33-year-old married woman was presented with an ulcerated and oozing mass of the right breast that had been evolving for one year. The examination noted an 8 cm irregular mass attached to the skin which it ulcerated. It was necrotic and foul smelling. Pathological anatomy noted a carcinomatous proliferation centred by keratogenic maturation. Immunohistochemistry was positive for AE1 and AE3 antibodies. The tumour was classified as cT4bN1bM0. It was triple negative. We performed a mastectomy and an axillary curage. Three out of 16 nodes were invaded. She is currently undergoing well-tolerated chemotherapy. Conclusion: Squamous cell carcinoma of the breast is a rare histological entity. The diagnosis is late like other breast cancers in Ouagadougou. Its prognosis remains poor. This is why early diagnosis, a better knowledge of its histogenesis and profile are important in order to better codify its management.